ANALISIS PENERAPAN BREAK EVEN POINT SEBAGAI ALAT PERENCANAAN LABA PADA PERUSAHAAN PT. KOPI JAYA CORPORA DI MAKASSAR - Ibrahim H. Ahmad (AkMen JURNAL ILMIAH, 2016)
The purpose of this study was to analyze the break even point applied by PT. Coffee Jaya Corpora in Makassar so it can be used as a planning tool. To achieve these objectives, the data collection techniques used through: observation, interviews and documentation, using data analysis techniques using the formula BEP, margin of safety, and contribution margin. Based on the results of the calculation of the BEP, which shows that the company's sales of coffee does not earn a profit and does not suffer a loss, then you should PT. Coffee Jaya Corpora should consider appropriate measures forecast or estimate. Based on the results analilsis margin of safety indicates that when the real selling less or deviate (from the planned sales) companies will suffer losses. Thus, it can be said that the smaller the margin of safety means that the faster the company suffered losses in this case is a real decline in sales.